2019
DOI: 10.20944/preprints201906.0205.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Different Salinities Gradient on Fatty Acid Composition, Growth, Survival and Reproductive Performance of Moina macrocopa (Straus 1820) (Crustacea, Cladocera)

Abstract: Salinity is a known factor which shapes population dynamics and community structure through direct and indirect effects towards aquatic ecosystems. The responses of Moina macrocopa (Cladocera) collected from Setiu Wetland lagoon (Terengganu) were evaluated through manipulative laboratory experiments to understand the ability of M. macrocopa to tolerate under high salinity stress. Specifically, the fatty acid composition, growth, survival and reproduction of this cladocerans species were examined. Sodium chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…Ngoài ra, Cladocera là nhóm quan trọng trong quần xã ĐVPS với hầu hết các loài phân bố trong môi trường nước ngọt ở độ mặn dưới 1‰ (Ghazy et al, 2009). Tốc độ tăng trưởng của M. macrocopa tăng lên trong điều kiện môi trường nước có độ mặn 0-6%, nhưng khi độ mặn tăng từ 8‰ đến 15‰ thì tốc độ tăng trưởng của chúng giảm thấp hơn (Rasdi et al, 2019).…”
Section: Thành Phần Loài Và Mật độ Của Cladocera Và Copepoda ở Các A...unclassified
“…Ngoài ra, Cladocera là nhóm quan trọng trong quần xã ĐVPS với hầu hết các loài phân bố trong môi trường nước ngọt ở độ mặn dưới 1‰ (Ghazy et al, 2009). Tốc độ tăng trưởng của M. macrocopa tăng lên trong điều kiện môi trường nước có độ mặn 0-6%, nhưng khi độ mặn tăng từ 8‰ đến 15‰ thì tốc độ tăng trưởng của chúng giảm thấp hơn (Rasdi et al, 2019).…”
Section: Thành Phần Loài Và Mật độ Của Cladocera Và Copepoda ở Các A...unclassified
“…Moina species may also be considered a promising species for feeding fish larvae and fingerlings as they have a short lifespan, abundant energy storage, small size, and short embryonic stage (Sipauba-Tavares et al, 2014;Samuel, 2014). Moina macroocopa is a cladoceran mostly found in water bodies and plays a role in food chains in the aquatic environment (Iannacone and Alvarino, 2000;Vignatti et al, 2013) and, has economic importance arising from its use in aquaculture as live food for fish larval stages (Vignatti et al, 2013;Rasdi et al, 2019). Tawaratmanikul (1988) reported that Clarius batrachus, Ompok bimaculatus, Lates calcarifer and Channa striatus fish larvae show improved growth and survival for cladorans as live feed (Amornsakun et al, 2001;Budhin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%